Dava um nervoso, dava um frio na barriga, sim: uma investigação da mobilização de estratégias afetivas por aprendentes de inglês do iema idiomas, durante as aulas remotas emergenciais, pela perspectiva da complexidade - VEIGA, Leandro Valente da (2022)
This study aims to investigate the mobilization of affective strategies by intermediate learners of English as an additional in a language center located in the city of São Luís MA, during the COVID-19 pandemic. For this purpose, we used as a theoretical framework Oxford’s (1990)language learning strategies, language anxiety (Tobias, 1986); (Horwitz et al, 1986) (MacIntyre and Gardner, 1989; 1994) and the affective filter hypothesis (KRASHEN 1985). Our research is guided by a concept of science from the complexity perspective (MORIN, 2005), as well as by the conception of language as a complex adaptive system. From the submission of learners to the Oxford (1990) inventory of language learning strategies, in addition to the writing of their learning narratives and a semi-structured interview, we sought, through thematic analysis, to identify affective issues that permeated these learners’ trajectory, with regard to the use of learning strategies, the presence (or not) of language anxiety, as well as the state of these learners’ affective filter, seeking to establish the relationship between these factors and their performance, especially in the period concerning the COVID pandemic -19. In our results, we could notice that, in general, with the COVID 19 pandemic and the change in the dynamics of classes to the learning remote model, new stressors were added to the practice of English learning, such as the concern with giving the classmates the impression of tiredness or discouragement, the lack of an adequate location and/or equipment to guarantee a more effective participation during the lessons, connectivity problems, having to turn on the camera and expose yourself or expose the place where you live, having the possibility of becoming a “meme”, having to carry all the attention to themselves every time they participate in the class, among others, which led learners either to intensify their use of affective strategies or to reduce their participation in classes. At the same time, among the learners who did not have any affective identification with the additional language or who did not use affective strategies to deal with the new challenges faced, we could notice a greater difficulty in the complex system in maintaining its stability.